2018
DOI: 10.1016/j.biomaterials.2018.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics facilitates the discrimination of the specific anti-cancer effects of free- and polymer-conjugated doxorubicin in breast cancer models

Abstract: Metabolomics is becoming a relevant tool for understanding the molecular mechanisms involved in the response to new drug delivery systems. The applicability of this experimental approach to cell cultures and animal models makes metabolomics a useful tool for establishing direct connections between in vitro and in vivo data, thus providing a reliable platform for the characterization of chemotherapeutic agents. Herein, we used metabolomic profiles based on nuclear magnetic resonance (NMR) spectroscopy to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 47 publications
3
23
0
1
Order By: Relevance
“…The differences in amino acids levels may relate to different growth kinetics, much faster for the 4T1 model therefore requiring more energy. Of note, several amino acids that exhibited lower concentrations in the MDA‐MB‐231‐Luc model metastatic lung (i.e., leucine, isoleucine and valine) are branched amino acids (BCAA) and studies have indicated an association between increased concentrations of BCAA and chemotherapy‐induced apoptotic processes . Interestingly, the ratio of choline/GPC indicates the acidic nature of metastatic tumors, since lower pH (typical of tumor cells) leads to decreased PC and increased GPC .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The differences in amino acids levels may relate to different growth kinetics, much faster for the 4T1 model therefore requiring more energy. Of note, several amino acids that exhibited lower concentrations in the MDA‐MB‐231‐Luc model metastatic lung (i.e., leucine, isoleucine and valine) are branched amino acids (BCAA) and studies have indicated an association between increased concentrations of BCAA and chemotherapy‐induced apoptotic processes . Interestingly, the ratio of choline/GPC indicates the acidic nature of metastatic tumors, since lower pH (typical of tumor cells) leads to decreased PC and increased GPC .…”
Section: Discussionmentioning
confidence: 99%
“…We also found several unique metabolic changes for each model. In 4T1 metastatic lungs, we discovered increased phenylalanine levels (related to advanced stages of the disease), aspartate (upregulated glutaminolysis) and ATP + ADP (fueling metastatic survival). Analysis of MDA‐MB‐231‐Luc metastatic lungs revealed a specific increase in glutathione levels, a molecule that plays protective and pathogenic roles and promotes chemoresistance, and GPC levels.…”
Section: Discussionmentioning
confidence: 99%
“…The chemosensitivity of in vitro cancer models is usually investigated by treatment with different concentrations of anticancer drugs (Armiñán et al, ; Langhans, ). In this study, we used various concentrations of paclitaxel (Sigma Aldrich) to treat our invasion cancer model.…”
Section: Methodsmentioning
confidence: 99%
“…The detailed analysis of single-cell metabolomics [ 173 , 174 ] may also highlight new targets, new triggers and mechanisms of therapeutic resistance for PT treatment [ 158 ]. Indeed, recent studies in our laboratory have shown distinct metabolic changes when comparing the treatment of breast cancer cells in vitro and in vivo in response to a chemotherapeutic anthracycline drug (Dox) and an HPMA copolymer-conjugated form (HPMA-Dox) [ 175 ]. Studies such as this, coupled with new advances in the understanding of cancer metabolism [ 176 ], may provide essential biomarkers for PT-based therapeutic approaches.…”
Section: Hurdle 5: Moving Towards the Finishing Line: Improved Detmentioning
confidence: 99%